Analisis Kegunaan Aplikasi Sistem Manajemen Acara dan Rapat Universitas Islam Nahdlatul Ulama Jepara Berdasarkan Metode System Usability Scale - Fanida Muta’aliyur Rohmah; Nadia Annisa Maori; Gentur Wahyu Nyipto Wibowo (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
The implementation of digital-based information systems in higher education aims to improve the effectiveness of academic and administrative activities. Universitas Islam Nahdlatul Ulama Jepara has implemented an Event and Meeting Management System application to support scheduling, agenda management, and documentation of institutional activities. This study aims to evaluate the usability level of the application using the System Usability Scale (SUS) method. The research employed a descriptive quantitative approach using the SUS questionnaire consisting of ten Likert-scale statements. A total of 200 active users, including university leaders, lecturers, administrative staff, and students, participated as respondents. The results show that the application obtained an average SUS score of 80.35, which is above the standard usability threshold of 68. These findings indicate that the Event and Meeting Management System application has a high level of usability and is easy to use by users. The results of this study are expected to provide valuable input for further system evaluation and development to enhance the effectiveness of academic and administrative management at the university.